Ethnic Russian Minority in Estonia - Włodarska-Frykowska, Agata (International Studies. Interdisciplinary Political and Cultural Journal, 2016)
The article examines the position of Russians in Estonia and their relation with ethnic Estonians. The author analyzes models of the society integration introduced by Tallinn after 1991. The results raise questions regarding language education in Estonia, the proficiency level of Estonian is getting widely known by Russians, but on the other hand, there is still a significant part of the population that cannot communicate in Estonian. Those who have a good command of Estonian tend to be better integrated and to coexist with both Estonians and Russians. Russians living in Estonia are supposed to be equally involved in social and political life of the state. The potential of all residents has to be effectively and considerably used, especially when the number of population is decreasing. The position of Russians in Estonia is a major domestic and bilateral issue in the relations with the Russian Federation.